Efforts To Improve Learning Outcomes On Self-Introduction Material Through PBL Learning Model (Problem Based Learning) In Class VII Of MTS N 1 Seluma - Dwisnu, Erlian (Early Childhood Research and Practice, 2025)
This research was motivated by students who found it difficult to answer questions given by the teacher, and it was still seen that students were less able to explain the answers well in learning English, so that in learning English students did not understand the lessons given by the teacher. The formulation of the problem in this research is whether by implementing the PBL learning model (Problem Based Learning) in the introduction material can improve learning outcomes in class VII MtS N 1 Seluma?. The purpose of this research is to determine student learning outcomes using the PBL learning model (Problem Based Learning) on instruction material in class VII MtS N 1 Seluma. This research uses Class Action Research (PTK) which observes the teaching and learning process in the classroom which is an examination of learning activities in the form of actions, which are deliberately created and occur in a class together. The data collection techniques used are observation and tests. Based on data analysis, the average student learning outcomes were obtained before using the PBL learning model (Problem Based Learning) namely 41% with only 11 people completing it and the remaining 16 people not completing it. After carrying out PTK with the PBL learning model (Problem Based Learning) The average student learning outcomes in cycle I reached 78% with 21 people getting a completion score above the KKM, namely 65. Cycle II further improved by achieving an average learning outcome reaching 100% with all students getting a completion score above The KKM is 65. So it can be concluded that the hypothesis can be proven by implementing the PBL learning model(Problem Based Learning) can improve learning outcomes in the introduction material in class VII MtS N 1 Selumacan be seen from student learning outcomes after carrying out PTK using the PBL learning model (Problem Based Learning) on introductory material with 100% classical completeness.